Age and engine displacement are associated with unsafe motorcycle rider actions. (September 2020) - Dubois, Sacha; Antoniazzi, Dylan; Klein, Rupert; Bédard, Michel
Highlights: We examined 29 years (1987–2015) of fatal U.S.A. crash data involving motorcycles. Unsafe Motorcyclist Actions (UMAs) were our proxy measure for crash responsibility. We computed odds ratios of an UMA by rider age and engine displacement. 56% committed one or more UMAs with Speeding and Weaving most frequently reported. Odds ratios of UMA were greatest for 750 CCs engines, followed by 500 and 1000 CCs. For specific UMAs, differences by age and engine displacement were observed. Abstract: Background : Our goal was to examine the relationship between age and engine displacement in cubic centimeters (CCs) and crash responsibility. Methods: Male motorcyclists, aged 16–94, involved in a fatal crash in the United States (1987–2015) who tested negative for both drugs and alcohol were included. Employing a case control design, cases had committed one or more Unsafe Motorcyclist Actions (UMAs), the proxy measure of responsibility; controls had no UMAs recorded. Odds ratios were computed via multinomial regression examining the effect of motorcyclists' age and motorcycle displacement (up to 1500 CCs, in 250 CC increments) on crash responsibility by any UMA and top three individual UMAs committed. Results: A total of 19, 166 motorcyclists met our inclusion criteria. Increased displacement was observed in older motorcyclists and in more recent crashes. Fifty-six percent of motorcyclists committed one or more UMAs (n = 10, 743). The top three individual UMAs were: Speeding (35%, n = 6, 728), Weaving (24%, n = 3, 269), and Erratic Operation (6%, n = 1, 162). Odds ratios for committing any UMA were the greatest for riders on 750 CC motorcycles, followed closely by 500 and 1000 CC motorcycles. By 1250 CCs the effect of displacement on rider crash responsibility (any UMA) was no longer statistically significant. Typically, younger ages (e.g., 20–30) on motorcycles with 500–1000 CCs were associated with the highest odds of either speeding, weaving, or erratic riding compared to similar aged riders on 250 CC motorcycles. Exceptions were observed, for example riders at 70 years of age on 1500 CCs having higher odds of speeding than younger riders on equivalent CC motorcycles. Conclusion: Education and legislative measures should be considered. Educationally, the development of training interventions focusing on control, stability, and breaking differences with more powerful motorcycles (750 to 1250 CCs) is needed. Legislatively, licensing tiers could be employed based on displacement and educational requirements. Education and legislative measures could help to curb the trend seen between high-powered motorcycles and crash responsibility.